Corporate Social Responsibility and Corporate Financial Performance: Evidence from Indian Capital Market - Viswanathan , Lakshmi (Asian Journal of Empirical Research, 2016)
The concept of corporate social responsibility (CSR) is welcomed with more enthusiasm in recent years. The present study, is a four phase investigation of the corporate financial performance of socially responsible firms relative to other firms, listed in Bombay Stock Exchange. We start with a comparative analysis of financial performance of CSR and non-CSR firms and then proceed to explore industry-specific effects. After identification of significant factors contributing to financial performance, we conduct an analysis to check for the feed-back effect on CSR using Probit model. We also compute the probability with which a firm is more likely to adopt CSR due to improvement in any of the significant factors.